182 Loss of Endothelial Endoglin Leads to Heart Failure. (3rd June 2016) - Tual-Chalot, Simon; Davison, Benjamin; Redgrave, Rachael; Arthur, Helen
Abstract : Introduction: Endoglin is a co-receptor for members of the transforming growth factor-beta superfamily of ligands, and regulates angiogenesis. Patients carrying mutations in the endoglin gene develop Hereditary Haemorrhagic Telangiectasia (HHT), a disorder characterised by vascular malformations and bleeding. Endoglin is mainly expressed in vascular endothelial cells, is required for normal blood vessel development, but its role in the adult vasculature is not yet understood. Methods: To investigate the role of endoglin in the adult vasculature, we used 12 week old Eng fl/fl ;  Cdh5Cre-ER T2 mice to generate endothelial-specific depletion of endoglin (Eng-iKO e ). Cardiac magnetic resonance imaging (MRI), vessel perfusion, vascular casting, immunohistology and qPCR were used to evaluate cardiovascular changes after endoglin knockdown. Results: Loss of endoglin leads to a massively enlarged heart and cardiomyocyte hypertrophy. These changes occur within 5 weeks of endoglin depletion. Cardiac output initially increases, but then the ejection fraction starts to fall, progressing to high output heart failure (HOHF) associated with increased cardiac expression of brain natriuretic peptide, atrial natriuretic peptide and alpha-skeletal actin. As HOHF may result from arteriovenous malformations (AVMs) or from anaemia, we first tested for these phenotypes in Eng-iKO e mice. However, we did not detect any AVMs in major organs or found evidence of anaemia to account for the rapid increase in cardiac output. On the other hand, we did observe defects in regulation of vascular tone that are currently under investigation. Conclusion: These data describe a novel phenotype and highlight the importance of endothelial endoglin in the maintenance of cardiac structure and function.